2020
DOI: 10.23889/ijpds.v5i1.1145
|View full text |Cite
|
Sign up to set email alerts
|

The Mortality After Release from Incarceration Consortium (MARIC): Protocol for a multi-national, individual participant data meta-analysis

Abstract: IntroductionMore than 30 million adults are released from incarceration globally each year. Many experience complex physical and mental health problems, and are at markedly increased risk of preventable mortality. Despite this, evidence regarding the global epidemiology of mortality following release from incarceration is insufficient to inform the development of targeted, evidence-based responses. Many previous studies have suffered from inadequate power and poor precision, and even large studies have limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…48 Methodologically, this approach allows for applying consistent inclusion/exclusion criteria applied across countries, an approach that has successfully been applied in other studies. [48][49][50] This method has several advantages, among others: (a) as data are analysed locally in the first step, it overcomes the privacy hurdles associated with sharing individual-level data across countries and jurisdictions; (b) involvement of local researchers provides an opportunity to convey the Open access nuances of local and national data; (c) allows for consistent and realistic adjustment for confounding factors that may explain differences in findings across countries; and (d) allows for increased clinical relevance of findings by providing the opportunity to explore clinical questions across different national contexts and times. 48 50 Objective 1: OMT adherence trajectories First, we will identify all OMT patients in each country.…”
Section: Analysis Strategymentioning
confidence: 99%
“…48 Methodologically, this approach allows for applying consistent inclusion/exclusion criteria applied across countries, an approach that has successfully been applied in other studies. [48][49][50] This method has several advantages, among others: (a) as data are analysed locally in the first step, it overcomes the privacy hurdles associated with sharing individual-level data across countries and jurisdictions; (b) involvement of local researchers provides an opportunity to convey the Open access nuances of local and national data; (c) allows for consistent and realistic adjustment for confounding factors that may explain differences in findings across countries; and (d) allows for increased clinical relevance of findings by providing the opportunity to explore clinical questions across different national contexts and times. 48 50 Objective 1: OMT adherence trajectories First, we will identify all OMT patients in each country.…”
Section: Analysis Strategymentioning
confidence: 99%
“…When individuals with OUD are released from confinement, they face a heightened risk of opioid overdose, stemming from the loss of habituation and physical tolerance that occurs when opioid use is interrupted during a period of incarceration. Indeed, numerous studies have identified the high risk of opioid overdose in the period immediately following discharge from prison [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“… 10 Additionally, the Mortality After Release from Incarceration Consortium (MARIC) has recently been established to examine mortality among people who have experienced incarceration internationally using individual participant data meta-analysis methods. 11 However, so far only a protocol of the Consortium has been published. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Open access (MARIC) has recently been established to examine mortality among people who have experienced incarceration internationally using individual participant data meta-analysis methods. 11 However, so far only a protocol of the Consortium has been published. 11 To our knowledge, no reviews have examined deaths among young people released from youth detention in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation